2021
DOI: 10.3389/fnsys.2021.709677
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Avalanches Across the Rat Somatosensory Barrel Cortex and the Effect of Single Whisker Stimulation

Abstract: Since its first experimental signatures, the so called “critical brain hypothesis” has been extensively studied. Yet, its actual foundations remain elusive. According to a widely accepted teleological reasoning, the brain would be poised to a critical state to optimize the mapping of the noisy and ever changing real-world inputs, thus suggesting that primary sensory cortical areas should be critical. We investigated whether a single barrel column of the somatosensory cortex of the anesthetized rat displays a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 66 publications
(111 reference statements)
2
29
0
Order By: Relevance
“…Our results have important implications in settings where we expect non-linear or out-of-equilibrium effects to be crucial, such as neural activity originated by external stimulation [30][31][32] or population growth [33][34][35]. Notably, it was shown that, in models with latent variables, phenomenological renormalization group approaches can give seemingly non-trivial results [36,37].…”
Section: Discussionmentioning
confidence: 70%
“…Our results have important implications in settings where we expect non-linear or out-of-equilibrium effects to be crucial, such as neural activity originated by external stimulation [30][31][32] or population growth [33][34][35]. Notably, it was shown that, in models with latent variables, phenomenological renormalization group approaches can give seemingly non-trivial results [36,37].…”
Section: Discussionmentioning
confidence: 70%
“…Using a neural probe with 32 microelectrodes (27 of them spanning across the cortex), we recorded stimulus-evoked responses from the barrel cortex in terms of both LFPs and spikes, mostly within MUA events (see Figure 1A and Section 4 for details on animal preparation, surgical implantation, whisker stimulation and data acquisition). In brief, the whisker corresponding to a recorded barrel column was deflected using a closed-loop controlled piezoelectric bender (Mariani et al, 2021 ) by administering 5 ms voltage pulses with a 10 s inter-stimulus interval to avoid adaptation phenomena in the somatosensory neural pathway. Deflections of different amplitudes (large, medium and small) were delivered corresponding, respectively, to voltage pulses of 2.8, 2.0, and 1.6 V at the input of the piezoelectric control system.…”
Section: Resultsmentioning
confidence: 99%
“…This system has the advantage of a one-to-one mapping of the sensory organ (the whisker) to a single cortical column (Diamond et al, 2008 ) which is experimentally accessible through an implanted shank-shaped multi-electrode array across cortical layers. Moreover, in the anesthetized animal, single whisker deflection can be operated by a piezoelectric device which allows for a tight control and fine tuning of the sensory input (Mariani et al, 2021 ). This experimental arrangement enabled us to investigate the capability of SNNs to classify whisker deflections of different amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The avalanche statistics is analyzed in LFPs data following standardized pipelines for their detection (see “ Methods ”) 2 , 5 , 40 , and we report a full statistical analysis of our dataset in 41 . The distribution p ( s ) of the avalanches sizes and of the avalanche duration p ( T ) are computed and fitted using a corrected maximum likelihood method 41 , 42 . We find that both are statistically compatible with the expected power-laws and as we show in Fig.…”
Section: Resultsmentioning
confidence: 99%